Rancang Bangun E-RPS Prodi Teknik Informatika IIB Darmajaya Berbasis Web - Dzaki Naufal, Muhammad (Jurnal Etnik: Ekonomi-Teknik, 2023)
The Semester Learning Plan (RPS) is a learning planning media that is structured as a guide for students in carrying out lecture activities to achieve the learning outcomes that have been set. The IIB Darmajaya Campus has a Semester Learning Plan (RPS) website which includes the faculty of computer science and the faculty of economics and business which is useful as a learning planning medium to guide students in carrying out lecture activities to achieve the learning outcomes that have been set. However, currently the Semester Learning Plans (RPS) that are used still use hardcopy storage, this is not effective due to lack of security and the hardcopy may be lost at a later date. This E-RPS website is a solution for managing and storing RPS. The purpose of this research is to provide a container as a media for managing and storing RPS online as well as more secure security and a more efficient management process. The method used is the ADDIE Research & Development (RnD) Model with the stages of questionnaire analysis and observation, system design taken from observations, development or system development, implementation, and also evaluation of the system that has been made using a questionnaire via the Google form. The end result of this research is to provide a forum in the form of an E-RPS website for informatics engineering study programs to make it easier for lecturers to manage RPS. The Semester Learning Plan management system is carried out entirely on the website without having to continuously update the SLP file via hardcopy if there is an update and more efficient value in storing the SLP file. It is hoped that for further development, this E-RPS website will have a validation feature in the form of a digital signature containing the Semester Learning Plan (RPS).